Signalling intertextuality in business emails. (April 2016) - Warren, Martin
Abstract: This study looks at the contribution of intertextuality to a text's coherence by examining the ways in which writers make use of recurrent words and phrases to signal instances of intertextuality in business emails. The data are a corpus of discourse flows comprised of two sets of interconnected emails read or written by two Hong Kong-based professionals. Key words and phrases in the corpus are identified using corpus linguistics software and then studied in context to determine whether they signal instances of intertextuality and, if so, whether they are predominantly used to signal prior or predicted texts. It is found that key words and phrases are associated with intertextuality and its directionality. The findings are also discussed in terms of how the power relations pertaining between the writer and reader influence the choice of language used and their wider implications for learning and teaching ESP. Highlights: Corpus of discourse flows of business emails collected from two professionals. Key words and phrases used to signal instances of intertextuality are identified. Alignment of key words and phrases with directionality of intertextuality examined. Influence of power relations on language used between writers and readers explored. Implications of the findings for ESP explored.